Regional security in the Middle East : a critical perspective - Bilgin, Pinar, 1971- (Routledge, Taylor & Francis Group, 2019)
In this new and fully revised edition Pinar Bilgin provides an accessible yet critical analysis of regional security in the Middle East. Using a non-realist approach, the author offers a comprehensive study of pasts, presents and futures of security in the region. The book distinguishes itself from previous (critical) studies on regional security by opening up both 'region' and 'security'. Different from those approaches that bracket one or the other, this study takes seriously the constitutive relationship between (inventing) regions, and (conceptions and practices of) security. There is not one Middle East but many, shaped by the insecurities of those who voice them. This book focuses on how present-day insecurities have their roots in practices that have, throughout history, been shaped by 'geopolitical inventions of security'. In doing so, the book lays the contours of a framework for thinking critically about regional security in this part of the world.